The SAGE handbook of human trafficking and modern day slavery - Clark, Jenny Bryson; Poucki, Sasha (SAGE reference, 2019)
Millions of people around the world are forced to work without pay and under threat of violence. These individuals can be found working in brothels, factories, mines, farm field, restaurants, construction sites and private homes: many have been tricked by human traffickers and lured by false promises of good jobs or education, some are forced to work at gunpoint, while others are trapped by phony debts from unscrupulous moneylenders. The SAGE Handbook of Human Trafficking and Modern-Day Slavery provides a comprehensive, interdisciplinary and global look at the diverse issues surrounding human trafficking and slavery in the post-1945 environment. Covering everything from history, literature and politics to economics, international law and geography, this Handbook is essential reading for academics and researchers, as well as for policy-makers and non-governmental organisations.